Suture Anchor Versus Transosseous Tunnel Repair for Inferior Pole Patellar Fractures Treated With Partial Patellectomy and Tendon Advancement: A Biomechanical Study. Issue 8 (12th August 2021) - O'Donnell, Ryan; Lemme, Nicholas J.; Marcaccio, Stephen; Walsh, Devin F.; Shah, Kalpit N.; Owens, Brett D.; DeFroda, Steven F.
Background: Comminuted inferior pole patellar fractures can be treated in numerous ways. To date, there have been no studies comparing the biomechanical properties of transosseous tunnels versus suture anchor fixation for partial patellectomy and tendon advancement of inferior pole patellar fractures. Hypothesis: Suture anchor repair will result in less gapping at the repair site. We also hypothesize no difference in load to failure between the groups. Study Design: Controlled laboratory study. Methods: Ten cadaveric knee extensor mechanisms (5 matched pairs; patella and patellar tendon) were used to simulate a fracture of the extra-articular distal pole of the patella. The distal simulated fracture fragment was excised, and the patellar tendon was advanced and repaired with either transosseous bone tunnels through the patella or 2 single-loaded suture anchors preloaded with 1 suture per anchor. Load to failure and elongation from cycles 1 to 250 between 20 and 100 N of force were measured, and modes of failure were recorded. Statistical analysis was performed using a paired 2-tailed Student t test. Results: The suture anchor group had less gapping during cyclic loading as compared with the transosseous tunnel group (mean ± SD, 6.83 ± 2.23 vs 13.30 ± 5.74 mm; P = .047). There was no statistical difference in the load to failure between the groups. The most common mode of failure was at the suture-anchor interface in the suture anchor group (4 of 5) and at the knot proximally on the patella in the transosseous tunnel group (4 of 5). Conclusion: Suture anchors yielded similar strength profiles and less tendon gapping with cyclic loading when compared with transosseous tunnels in the treatment of comminuted distal pole of the patellar fractures managed with partial patellectomy and patellar tendon advancement. Clinical Relevance: Suture anchors may offer robust repair and earlier range of motion in the treatment of fractures of the distal pole of the patella. Clinical randomized controlled trials would help clinicians better understand the difference in repair techniques and confirm the translational efficacy in clinical practice.